Capturing Complexity Complexities in Health Promotion Intervention Research: Conducting Critical Realist Evaluation realists Evaluation - Frohlich, Katherine L.; St-Arneault, Kate; St-Pierre, Mikael (Global Handbook of Health Promotion Research, Vol. 1: Mapping Health Promotion Research, 2022)
The circumstances in which everyday life takes place shapes people’s capacity to lead healthy lives. We posit that the traditional linear way of thinking about causes and consequences limits our ability to fully capture the complexity of the interaction between people and their contextual circumstances in the production of health. We view critical realism as particularly helpful in understanding how problems are generated by this interaction as well as understanding the fit and responsiveness of our interventions to situational contexts. Such a perspective requires systematically attempting to “unpack” how different settings are shaped by health promotion interventions and how this is experienced by people. Accessing and mobilising such knowledge also requires particular sets of methods that deviate from what is still often seen as the gold standard for designing and evaluating interventions. Critical realism therefore shifts the primary focus of health promotion research from questions about “if” interventions work to questions about “how”, “why” and “under what circumstances” they can work. By helping to capture complexity in health promotion intervention research, a critical realist perspective leads to the production of rigorous knowledge without having to succumb to concerns about standardisation.
Keywords: Healthy cities; Outdoor free-play; Participatory planning